Blockade of PD-1 and LAG-3 expression on CD8+ T cells promotes the tumoricidal effects of CD8+ T cells - Ma, Jiajia; Yan, Shufang; Zhao, Ying; Yan, Huifang; Zhang, Qian; Li, Xinxia (Frontiers in Immunology, 2023)
The diffuse large B-cell lymphoma (DLBCL) has the highest incidence of all lymphomas worldwide. To investigate the functions of lymphocyte activation gene 3 (LAG-3) and programmed cell death 1 (PD-1) in tissues and peripheral blood of patients with DLBCL, the expression of LAG-3 and PD-1 genes in DLBCL-TCGA were analyzed.Methods: LAG-3 and PD-1 mRNA levels in DLBCL were analyzed using data from The Cancer Genome Atlas (TCGA) database. Utilize the Genotype-Tissue Expression (GTEx) database for assessing the variance in the expression of LAG-3, PD-1, and other associated factors between the tissues of DLBCL patients and healthy individuals. Immunohistochemistry was applied to detect the expression of LAG-3 and PD-1 levels in 137 cases of DLBCL tissues and 20 cases of reactive lymphoid hyperplasia. The prognostic value of LAG-3 and PD-1 were assessed using the Kaplan-Meier curve. The Estimation of Stromal and Immune cells in Malignant Tumor tissues using Expression data (ESTIMATE) and ssGSEA algorithm were used to explore the immune microenvironment of DLBCL. Additionally, the expression and co-expression of LAG-3 and PD-1 were detected on CD4 and CD8 T cells in peripheral blood samples from 100 cases of DLBCL tissues and 30 cases of healthy individuals using flow cytometry.Results: According to TCGA database, LAG-3 and PD-1 gene expression levels were significantly upregulated in DLBCL tissues. LAG-3 and PD-1 levels were also strongly positively correlated with those of most infiltrating immune cells. Overall survival of patients with high LAG-3 and PD-1 coexpression was significantly shorter than that of patients with low co-expression. In DLBCL patients, LAG-3 and PD-1 were highly expressed in peripheral blood CD8 + T cells. In addition, LAG-3 was highly expressed in CD4 + T cells, while the expression of PD-1 in CD4 + T cells of DLBCL patients showed no significant difference compared to healthy individuals. Conclusions: High LAG-3 and PD-1 levels significantly inhibit CD8 + T cell function, resulting in weakened ability to kill tumor cells. Combined LAG-3 and PD-1 blockade can restore CD8 + T cell function and provides a potential avenue for development of personalized cellular immunotherapy for DLBCL.